High gain approach and sliding mode control applied to quadrature interferometer - Felão, Luiz Henrique Vitti (2019)
Interferometers are extremely sensitive measurement devices, which use the principle of interference between two or more sources of light to generate a pattern of constructive and destructive interference. This pattern contains information about the physical phenomenon under study, and their light intensity can be used to calculate the optical path difference traveled by the two beams. The optical path difference and light intensity relationship is given by a cosine type function. Large disturbances can change the interferometer operation point, reaching nonlinear regions of the interferometric curve and even inducing ambiguities due to the periodicity of the input/output relationship. The present work concerns with the modeling, development and application of a control strategy based on sliding mode control, in a two-beam quadrature interferometer. It was used the high gain approach, which consists in to fully compensate the phase shifts induced on the sensor arm with the control system, in such a way that the voltage control signal becomes proportional to the phase disturbances. Therefore, the demodulation process does not require phase unwrapping algorithms. This implemented system showed capability to improve dynamic range and bandwidth when compared with other control systems in literature that were based on different high gain approach topologies. Also a new method of interferometric phase demodulation is proposed allying this control strategy to a virtual emulated interferometer. This allows keeping the real interferometer in open-loop and retrieving the phase shift information from the control signal of the virtual closed-loop interferometer, thus leading to considerable simplification of the required instrumentation. An ellipse fitting algorithm was applied to the system, allowing the correction of the Lissajous figure formed by both output interferometric signals from an ellipse to a unitary circle. Therefore, the system estimates the phase shift even with quadrature mismatches. Inertial sensors such as accelerometers and gyroscopes can benefit from this system in two major points: first, the sensitivity can be increased without limiting the end of scale of the sensor due to the proportional relation of the voltage control signal and the measured phase shift; and second, the system can be implemented without the need of PZT feedback actuators or modulators and PZT driven circuitry, reducing cost, volume and weight of the sensors.